Investment Activity of Commercial Banks and its Mechanisms of Formation - Khasanova Shahzoda Makhmatmurod kizi (Scientific Trends, 2023)
This article describes the role of commercial banks in the conditions of the developing market economy, the state of banks in Uzbekistan and the development prospects. The economic importance and conditions of banks in the formation of the financial base of the state have been analyzed and results have been given.
Keywords: Digital economy, commercial bank, economy, credit, finance, investment, liquidity, deposit, securities.